Mechanical and durability properties of medium strength self-compacting concrete with high-volume fly ash and blended aggregates - Nagaratnam, Brabha H; Faheem, Ahmed; Muhammad Ekhlasur, Rahman; Mohammad Abdul, Mannan; Leblouba, Moussa (Technical University of Budapest, 2015)
This research investigates the fresh state properties and hardened state properties of medium strength, self-compacting concrete incorporating a high volume of class F fly ash as a partial replacement to cement and blended fine aggregates while maintaining satisfactory properties of SCC. The properties of self-compaction investigated are: slump flow, J-ring, L-box, V-funnel, sieve stability and Visual Stability Index tests. Those of hardened concrete include compressive strength, splitting tensile strength, complete immersion water absorption, apparent volume of permeable voids, sorptivity, and rapid chloride ion penetration tests. The experiments on fresh state properties investigate the filling ability, the passing ability and the segregation resistance of concrete. The results show that fly ash improves workability and decreases the compressive strength as well as splitting tensile strength. Fly ash based SCC shows better resistance to water absorption, apparent volume of permeable voids, sorptivity, and chloride penetration than the control mix.